Allenylidene Induced 1, 2‐Metalate Rearrangement of Indole‐Boronates: Diastereoselective Access to Highly Substituted Indolines. (22nd April 2021) - Simlandy, Amit Kumar; Brown, M. Kevin
Abstract: A process to achieve 1, 2‐metalate rearrangements of indole boronate as a way to access substituted indolines in high diastereoselectivities is presented. The reaction involves the generation of a Cu–allenylidene, which is sufficiently electrophilic to induce the 1, 2‐metalate rearrangement. The scope of the reaction is evaluated as well as further transformations of the product. Abstract : A new class of electrophile, Cu–allenylidene has been introduced to induce 1, 2‐metalate rearrangement. Merger of Cu‐catalyzed propargylation and 1, 2‐boronate shift has allowed access to densely functionalized chiral indolines with up to three contiguous stereogenic centres in highly diastereoselective fashion (>20:1 dr ). Utility of Bpin and alkyne moieties has been demonstrated by subsequent synthetic elaborations.